STUDI POTENSI PENGEMBANGAN RUANG TERBUKA HIJAU DI KAWASAN TEPIAN SUNGAI KAPUAS, SINTANG, KALIMANTAN BARAT - Situmorang, Yosua Teguh; Suryadjaja, Regina (Jurusan Arsitektur dan Perencanaan, 2024)
One of the regencies in the province of West Kalimantan is Sintang Regency. Within Sintang Regency, there are two major rivers that cross over: the Kapuas River and the Melawi River The local community refers to the point where these two large rivers meet as “Saka Tiga.” One of the green open spaces in Sintang Regency is Taman Bungur (Bungur Park). Taman Bungur is a green open space located along the Kapuas River, covering an area of 1.3 hectares with a length of 336 meters and a width of 40 meters. Since the COVID-19 pandemic until now, visitor activities in Taman Bungur remain sparse due to neglected facilities within the park area. Additionally, culinary activities, which used to be an attraction for visitors, are no longer available. As a result, Taman Bungur has become somewhat neglected, contributing to the decline in visitors. Recognizing the potential of Taman Bungur as the only riverside park in Sintang, it becomes an attraction for visitors. Therefore, a study is needed to explore the development potential of green open space along riverbanks, considering ecological, economic, and aesthetic aspects to maximize its potential. This qualitative study employs descriptive analysis, including site analysis, location assessment, benchmarking, SWOT, and spatial potential analysis, aiming to optimize the riverbank green open space. The study’s findings will serve as a reference for the Sintang Regency government in conceptualizing riverbank development. Keywords: city park; development; green open space; kapuas river; river side Abstrak Kabupaten Sintang merupakan salah satu Kabupaten yang ada di Provinsi Kalimantan Barat, yang dilewati oleh dua sungai besar yaitu Sungai Kapuas dan Sungai Melawi. Masyarakat sekitar menyebut titik bertemunya dua sungai besar tersebut dengan sebutan